Social Marketing in Action - Basil, Debra Z.; Diaz-Meneses, Gonzalo; Basil, Michael D. (Springer, 2019)
This book was written for those interested in creating social change for the greater good. In this book, we provide a wide selection of social marketing cases from which we can learn and teach. The book is intended for both academic and practitioner use. Part I of this book offers a brief yet comprehensive review of social marketing. This provides the reader with the background in social change and marketing necessary to read and analyze the subsequent cases. Parts II, III, IV, and V of this book offer a total of 24 social marketing cases, from a variety of countries, addressing many different issues. For classroom use, this book is written to serve as a stand-alone tool, with Part I providing a concise introduction to social marketing principles and theory. Chapter appendices provide links to further readings on social marketing principles for those wishing to delve deeper. If still further detail on social marketing principles and theory are desired, this book can easily be paired with another social marketing textbook as well. We have aimed the book to be accessible to undergraduate students but also offer sufficient material to challenge students at the graduate level. Advanced students should be encouraged to further explore the references and links provided, to critique the case approaches, and to offer alternative strategies for the cases provided. A separate teaching guide collection is available for the book as well. This collection contains answers to the discussion questions in the cases, as well as suggested activities for inside and outside of the classroom. Additionally, the teaching guides for many cases offer suggestions for further reading and other helpful resources. For practitioner use, Part I offers a refresher on basic social marketing principles. In addition, a variety of references are offered, allowing for further personal study. Parts II through V offer detailed information about a wide variety of actual social marketing programs. You can compare and contrast these cases with your own situation, hopefully gaining insights that will be helpful in your own social marketing efforts.
Cases from Around the World